Pengaruh Kinerja Keuangan Dan Inflasi Terhadap Tingkat Bagi Hasil Deposito Mudharabah Pada Bank Umum Syariah - Ida Ayu Rahmatika; Jacobus Widiatmoko (Universitas Pendidikan Ganesha, 2022)
This research amied to examine the effect of ROA, FDR, OER/BOPO, and inflation toward the rate of return mudharabah deposit islamic bank in Indonesia on 2015-2019. This research use quatitative method and the data use is secondary data. Sampling technique in this research use purposive sampling method. The sampel in this research is 11 islamic bank has been registered in OJK on 2015-2019. The method use in this research is multiple linier regression. The result of this research show that (1) ROA, FDR, BOPO, and inflation simultaneously has a effect on the rate of return mudharabah deposits. (2) ROA and BOPO partially has no effect and significant on the rate of return mudharabah deposits. (3) FDR partially has a positive and significant effect on the rate of return mudharabah deposits. (4) Inflation partially has a negative significant effect on the rate of return mudharabah deposits.